DINAMIKA PENGANGGARAN DAERAH: ANALISIS PIERRE BOURDIEU TENTANG PERTARUNGAN POLITIK DAN KONFLIK KEPENTINGAN STAKEHOLDER - Faisal, Andi; Adriansyah, Adriansyah; Yusuf, Yulia Yunita (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the dynamics of budgetary battles between the executive and legislative branches in North Toraja Regency, using Pierre Bourdieu’s theory of habitus and capital as the analytical framework. The regional budgeting process often becomes a battleground between two competing parties seeking favorable budget allocations to advance their political interests. Employing a qualitative case study approach, data were collected through in-depth interviews with local government officials, members of the regional legislature (DPRD), and community leaders directly involved in budget decision-making. The findings reveal that political actors both executive and legislative utilize political capital, social capital, and symbolic capital to advocate for their interests during the budgeting process, which frequently results in political compromises that sacrifice public needs. The use of habitus, shaped by local social and cultural experiences, also plays a significant role in shaping the perceptions and actions of political actors in the budgeting process. The study finds that regional budgeting in North Toraja is influenced not only by public needs but also by personal and group interests, leading to inefficient, non-transparent, and unaccountable budget allocations. This research contributes to a deeper understanding of regional budget dynamics and offers recommendations for improving transparency and accountability in the budgeting process.